2001
DOI: 10.1002/eat.1038
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in haptic perception and right parietal theta power changes in patients with anorexia nervosa before and after weight gain

Abstract: The quality of reproduction of the haptic stimuli and the theta-power changes indicate a cortical dysfunction and deficits in somatosensory integration processing of the right parietal cortex in AN patients even after weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 29 publications
8
78
1
2
Order By: Relevance
“…Consistent with this notion, previous studies have observed neuropsychological deficits in patients with anorexia nervosa in attentional, visuospatial, motor and problem solving tasks, but not in memory tasks. [45][46][47] Grunwald and colleagues 48,49 observed a deficit in the reproduction of haptic stimuli in patients with anorexia nervosa. They interpreted these findings in terms of a deficit in somatosensory integration processing of the parietal cortex.…”
Section: Stgmentioning
confidence: 99%
“…Consistent with this notion, previous studies have observed neuropsychological deficits in patients with anorexia nervosa in attentional, visuospatial, motor and problem solving tasks, but not in memory tasks. [45][46][47] Grunwald and colleagues 48,49 observed a deficit in the reproduction of haptic stimuli in patients with anorexia nervosa. They interpreted these findings in terms of a deficit in somatosensory integration processing of the parietal cortex.…”
Section: Stgmentioning
confidence: 99%
“…[17][18] Some of these studies have lacked a normal control group (NC) 7,12 thereby limiting these findings. Cognitive deficits in AN may be the consequence of factors other than nutritional deficiency, 1 as a number of studies have neither demonstrated amelioration following nutritional restoration [4][5][6][19][20][21][22] nor correlation with low body mass indices (BMI). 7,23 Although the remission of physical symptoms in AN generally precedes psychological recovery, 24 findings regarding the effect of weight-recovery on neuropsychological function in AN have been conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the hypothesis of malnutrition does not explain the cognitive deficits found in groups with BN. In addition, recent studies indicate that certain cognitive functions do not improve after refeeding or weight gain (Green et al, 1996, Grunwald et al, 2001Hamsher et al, 1981;Katzman et al, 2001, Kingston et al, 1996Szmukler et al, 1992), and do not correlate with BMI (Bayless, 2002). Thus, it can be suggested that neuropsychological deficits in various cognitive domains preexist before the development of an ED and are not a consequence of the disorder.…”
Section: Resultsmentioning
confidence: 99%